A COMPENSATED-REDLICH-KWONG (CORK) EQUATION FOR VOLUMES AND FUGACITIES OF CO2 AND H2O IN THE RANGE 1 BAR TO 50 KBAR AND 100-1600°C - Holland T.; Powell R. (My University, 1991)
We present a simple virial-type extension to the modified Redlich-Kwong (MRK) equation for calculation of the volumes and fugacities of H2O and CO2 over the pressure range 0.001–50 kbar and 100 to 1400°C (H2O) and 100 to 1600°C (CO2). This extension has been designed to: (a) compensate for the tendency of the MRK equation to overestimate volumes at high pressures, and (b) accommodate the volume behaviour of coexisting gas and liquid phases along the saturation curve. The equation developed for CO2 may be used to derive volumes and fugacities of CO, H2, CH4, N2, O2 and other gases which conform to the corresponding states principle. For H2O the measured volumes of Burnham et al. are significantly higher in the range 4–10 kbar than those presented by other workers. For CO2 the volume behaviour at high pressures derived from published MRK equations are very different (larger volumes, steeper (?P/?T)V, and hence larger fugacities) from the virial-type equations of Saxena and Fei. Our CORK equation for CO2 yields fugacities which are in closer agreement with the available high pressure experimental decarbonation reactions.